FRACTIONATION OF MAJOR ELEMENTS BETWEEN COEXISTING H2O-SATURATED SILICATE MELT AND SILICATE-SATURATED AQUEOUS FLUIDS IN ALUMINOSILICATE SYSTEMS AT 1-2 GPA - Mysen B.O.; Shang J. (My University, 2003)
From experimental data in the systems Na2O-Al2O3-SiO2-H2O, K2O-Al2O3-SiO2-H2O at 1100°C, and CaO-Al2O3-SiO2-H2O at 1200°C in the 1-2 GPa pressure range, the solution behavior of the individual oxides in coexisting H2O-saturated silicate melts and silicate-saturated aqueous fluids appears to be incongruent. Recalculated on an anhydrous basis, in the CaO-Al2O3-SiO2-H2O system, CaOfluid/CaOmelt < 1, whereas in the Na2O-Al2O3-SiO2-H2O and K2O-Al2O3-SiO2-H2O systems, K2Ofluid/K2Omelt and Na2Ofluid/Na2Omelt both are greater than 1. The aqueous fluids are depleted in alumina relative to silicate melt.In the Na2O-Al2O3-SiO2-H2O, K2O-Al2O3-SiO2-H2O, and CaO-Al2O3-SiO2-H2O systems, fluid/melt partition coefficients for the individual oxides range between ~0.005 and 0.35 depending on oxide, bulk composition and pressure. The alkali partition coefficients are about an order of magnitude higher than that of CaO. Alumina and silica partition coefficient values in the CaO-Al2O3-SiO2-H2O system are 10-20% of the values for the same oxides in the Na2O-Al2O3-SiO2-H2O and K2O-Al2O3-SiO2-H2O systems.Positive correlations among individual partition coefficients and oxide concentrations in the aqueous fluids are consistent with complexing in the fluid that involves silicate polymers associated with alkalis and alkaline earths and aluminosilicate complexes where alkalis and alkaline earths may serve to charge-balance Al3+, which is, perhaps, in tetrahedral coordination. Alkali aluminosilicate complexes in aqueous fluid appear more stable than Ca-aluminosilicate complexes.